DISTANCE LEARNING FOR HIGHER EDUCATION: A LITERATURE REVIEW - Abdul Wahab Syakhrani; Mohammad Ahmad Bani Amer; Rosijanih Arbie (International Journal of Teaching and Learning, 2025)
Distance learning (DL) in higher education has undergone significant development, especially during emergency situations such as pandemics. This abstract discusses a literature review of the implementation, benefits, and challenges of DL in the context of higher education. The main findings show that DL offers flexibility in time and place of learning, as well as improving students' digital skills. However, challenges in the form of technology access gaps and decreased social interaction are obstacles that must be overcome. In conclusion, although DL presents several obstacles, with proper management and adequate infrastructure support, it has the potential to become an important element in providing effective and inclusive education in the future.